Action on the social determinants for advancing health equity in the time of COVID-19: perspectives of actors engaged in a WHO Special Initiative - Orielle Solar; Nicole Valentine; Antia Castedo; Gonzalo Soto Brandt; Jaitra Sathyandran; Zahra Ahmed; Paul Cheh; Emma Callon; Felicity Porritt; Isabel Espinosa; Kira Fortune; Shogo Kubota; et al. (BMC, 2023)
Abstract Since the 2008 publication of the reports of the Commission on Social Determinants of Health and its nine knowledge networks, substantial research has been undertaken to document and describe health inequities. The COVID-19 pandemic has underscored the need for a deeper understanding of, and broader action on, the social determinants of health. Building on this unique and critical opportunity, the World Health Organization is steering a multi-country Initiative to reduce health inequities through an action-learning process in 'Pathfinder' countries. The Initiative aims to develop replicable and reliable models and practices that can be adopted by WHO offices and UN staff to address the social determinants of health to advance health equity. This paper provides an overview of the Initiative by describing its broad theory of change and work undertaken in three regions and six Pathfinder countries in its first year-and-a-half. Participants engaged in the Initiative describe results of early country dialogues and promising entry points for implementation that involve model, network and capacity building. The insights communicated through this note from the field will be of interest for others aiming to advance health equity through taking action on the social determinants of health, in particular as regards structural determinants.